POWER SAVER STREET LIGHTING USING MICROCONTROLLER USING ATmega16 - Sharma, Karan; Mandil, Kunal; Gupta, Nancy (International Journal of Engineering Technologies and Management Research, 2018)
Street lights remain illuminated for whole nights and most of them used for lighting-up of highways are high energy consumption lamps. Preservation and sustainable use of energy and resources is an important factor of planning and development these days as Natural resources are depleting day by day, which pose a risk of scarcity and non-availability of the same for our presidenting generations. There is an acute need for devising a well thought out plan to prevent wastage of electricity. Perhaps, the government should think of implementing automatic street light control systems using LDR (light dependent resistor). This review paper illustrates the street light illumination system automated by the movement (frequency) of vehicles on that particular street. The crux of this paper is to emancipate the necessity and usage of street light control systems which combines various technologies is Timers, Photodiodes, Light Emitting Diodes (LED), and IR Sensors.